Skutki podatkowe pracy w ramach sztucznej inteligencji – wybrane aspekty - Szczepańska, Ilona (PRAWO i WIĘŹ, 2026)
The aim of this paper is to present the tax consequences of work within artificial intelligence. For its implementation, reference was made to the general assumptions of taxation of individuals, taking into account tax preferences, with research and development activities being given importance. The methodology adopted to achieve the research objective is based on the analysis of legal regulations on IP BOX and R&D relief, tax explanations, individual interpretations and the case law of administrative courts. The analysis conducted concerns mainly the provisions of substantive tax law and judgments of administrative courts and, to a small extent, individual interpretations of tax law provisions. The author’s intention was to present solutions in the sphere of legal and tax regulations shaped in the context of personal income tax, which can be used by individuals creating projects related to artificial intelligence, or contributing to or using artificial intelligence.